Manganese oxide nanodot / carbon material and preparation method and application thereof

By using manganese oxide nanodot/carbon materials in the positive electrode material of aqueous zinc ion battery, the problems of poor conductivity of manganese oxides and easy structure collapse are solved, high specific capacity, good rate performance and long cycle stability are achieved, and the process is simple and cost is low.

CN119297259BActive Publication Date: 2025-04-25LIAOCHENG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411793109.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-25
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

Manganese oxides have poor conductivity, easy structure collapse and easy dissolution in the positive electrode materials of aqueous zinc ion batteries, resulting in poor specific capacity and cycle stability.

Method used

Manganese oxide nanodot/carbon material is used, which consists of a sheet-like carbon matrix material and manganese oxide nanoparticles distributed thereon, and is prepared by freeze-drying and calcining treatment. The explosion effect of perchlorate is used to form depressions on the carbon matrix material, which promotes the formation and uniform dispersion of manganese oxide nanoparticles.

Benefits of technology

It significantly improves the conductivity of manganese oxide, inhibits the collapse of manganese oxide structure, and improves the specific capacity, rate performance and cycle stability of zinc ion batteries. At the same time, it is simple in process and low in cost, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297259B_ABST
    Figure CN119297259B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of zinc ion battery positive electrode material preparation, and specifically discloses a manganese oxide nanodot / carbon material, a preparation method thereof, and an application thereof. The manganese oxide nanodot / carbon material comprises a flaky carbon matrix material and manganese oxide nanoparticles distributed on the matrix material, and a plurality of pit-shaped depressions are distributed on the matrix material. The preparation method comprises the following steps: adding a carbon source, a perchlorate, and a manganese source to water and stirring evenly, freeze-drying the obtained precursor liquid, and then calcining the obtained solid product in a protective atmosphere, and washing and drying the obtained product after completion. The material of this morphology prepared by the present invention can significantly improve the conductivity of manganese oxide, and when used as a positive electrode of a zinc ion battery, it helps to inhibit the collapse of the manganese oxide structure, so that the zinc ion battery has long cycle stability, excellent specific capacity and rate performance, and improves the energy storage characteristics of the zinc ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of zinc ion battery positive electrode material preparation, and in particular to a manganese oxide nanodot / carbon material, a preparation method and an application thereof. Background Art

[0002] The progress of energy storage technology can not only improve the utilization efficiency of clean energy, but also promote the development of emerging industries and promote the transformation of green economy, which will provide strong support for coping with global climate change and achieving sustainable development goals. Aqueous zinc ion batteries (AZIBs) have shown excellent performance, with a theoretical specific capacity of up to 820 mAh / g and 5855 mAh / cm 3 , and has a low redox potential (about -0.76 V relative to the standard hydrogen electrode), so it can provide energy density similar to that of lithium-ion batteries. In addition, metallic zinc is not only abundant in nature, environmentally friendly, but also low in cost, which makes it have significant application potential in the field of large-scale energy storage. Zinc-ion batteries are expected to form a good complementary relationship with lithium-ion batteries, and even replace the latter in some cases, promoting the development of energy storage technology.

[0003] In AZIBs, since metallic zinc can be directly used as the negative electrode, the specific capacity of the positive electrode directly determines the electrochemical performance of AZIBs. Manganese oxides (such as MnO, MnO2, Mn2O3 and Mn3O4) have the advantages of abundant reserves, high theoretical capacity, high operating voltage, low cost, and environmental protection, and are the most ideal positive electrode materials in AZIBs. However, manganese oxides also have certain defects when used as positive electrode materials for aqueous zinc-ion batteries, such as poor conductivity, easy structural collapse, and easy dissolution of manganese oxides, resulting in the specific capacity and cycle stability of manganese oxide materials not reaching the expected level. Summary of the invention

[0004] In view of the above problems, the present invention provides a manganese oxide nanodot / carbon material and a preparation method and application thereof, which, when used as a positive electrode material for aqueous zinc ion batteries, has excellent specific capacity, rate performance and long cycle stability. Specifically, the technical solution of the present invention is as follows.

[0005] Firstly, the present invention provides a manganese oxide nanodot / carbon material, which comprises a flaky carbon matrix material and manganese oxide nanoparticles distributed on the matrix material, and a plurality of pit-shaped depressions are distributed on the matrix material.

[0006] Furthermore, the thickness of the flaky carbon matrix material ranges from 10 to 100 nm.

[0007] Furthermore, the diameter of the manganese oxide nanoparticles is 2-30 nm.

[0008] Secondly, the present invention provides a method for preparing manganese oxide nanodots / carbon materials, comprising the following steps: adding a carbon source, a perchlorate and a manganese source into water and stirring them evenly, freeze-drying the obtained precursor liquid, and then calcining the obtained solid product in a protective atmosphere. After completion, the obtained product is washed and dried to obtain the obtained material.

[0009] Furthermore, the mass ratio of the carbon source, the perchlorate and the manganese source is 10:(0.1-2):(0.5-25). The water can fully dissolve the carbon source, the perchlorate and the manganese source.

[0010] Furthermore, the manganese source includes at least one of manganese nitrate, manganese sulfate, manganese carbonate, manganese chloride, manganese acetate, etc.

[0011] Furthermore, the carbon source includes at least one of α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin and the like.

[0012] Furthermore, the perchlorate includes at least one of lithium perchlorate, sodium perchlorate, potassium perchlorate, etc.

[0013] Furthermore, the calcination treatment temperature is 600-1000°C, and the holding time is 1-6 hours. Optionally, the protective atmosphere includes any one of inert gases such as nitrogen and argon.

[0014] Finally, the present invention provides the application of the manganese oxide nanodots / carbon material in the positive electrode of an aqueous zinc ion battery.

[0015] Compared with the prior art, the present invention has the following beneficial technical effects:

[0016] When the precursor solution formed by the carbon source, perchlorate and manganese source is freeze-dried, the perchlorate molecules are allowed to enter the cage of the cyclodextrin by utilizing the attraction of cyclodextrin to alkali metal ions. In the subsequent calcination process, the perchlorate will explode to peel the carbon material formed by the cyclodextrin into a flaky carbon matrix material, and due to the local explosion effect of sodium perchlorate, a crater-shaped depression is formed on the carbon material. This depression will preferentially attract the formation of manganese oxide nanoparticles, and because the explosion effect of the perchlorate helps the manganese oxide nanoparticles to maintain a smaller size, not only the activity is higher, but also it helps to be evenly dispersed on the flaky carbon matrix material. The material of this morphology prepared by the present invention can significantly improve the conductivity of manganese oxide, and when used as the positive electrode of a zinc ion battery, it helps to inhibit the collapse of the manganese oxide structure, so that the zinc ion battery has long cycle stability, excellent specific capacity and rate performance, and improves the energy storage characteristics of the zinc ion battery. In addition, the method for preparing manganese oxide nanodots / carbon material of the present invention has a simple process flow, is easy to operate, does not require the use of organic solvents, has low production costs, and is easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. The embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein:

[0018] Figure 1 This is the X-ray powder diffraction pattern of the manganese oxide / carbon material prepared in Example 1.

[0019] Figure 2 This is a scanning electron microscope image of the manganese oxide / carbon material prepared in Example 2, magnified 10,000 times.

[0020] Figure 3 This is a scanning electron microscope image of the manganese oxide / carbon material prepared in Example 2, magnified 200,000 times.

[0021] Figure 4 This is a transmission electron microscope image of the manganese oxide / carbon material prepared in Example 3.

[0022] Figure 5 This is a detailed spectrum of manganese element in the X-ray photoelectron spectroscopy (XPS) of the manganese oxide / carbon material prepared in Example 4.

[0023] Figure 6 This is the charge and discharge curve of the zinc ion battery assembled in Example 5 at a current density of 200 mA / g.

[0024] Figure 7 This is the charge and discharge curve of the zinc ion battery assembled in Example 5 at a high current density of 5 A / g.

[0025] Figure 8 This is the cycling curve of the zinc ion battery assembled in Example 6 at a current density of 200 mA / g.

[0026] Fig. 9 This is the cycling curve of the zinc ion battery assembled in Example 7 at a high current density of 1 A / g. DETAILED DESCRIPTION

[0027] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0028] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. If not otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the described content can be applied to the method of the present invention. Now, the present invention is further described in conjunction with the accompanying drawings and specific embodiments of the present invention, and the preferred implementation methods and materials described in the present invention are only for demonstration purposes.

[0029] Example 1

[0030] A method for preparing manganese oxide nanodots / carbon material comprises the following steps:

[0031] (1) Weigh 10 g of α-cyclodextrin, 0.25 g of lithium perchlorate, and 2.2 g of manganese acetate respectively, add them into a beaker containing 100 mL of distilled water, and continue stirring to form a colorless transparent solution. Freeze the colorless solution and place it in a vacuum freeze dryer until it is completely dry to obtain a precursor.

[0032] (2) placing the precursor in a tube furnace, heating it to 700°C at a heating rate of 5°C / min under an argon atmosphere and keeping the temperature for 2 h. After completion, cooling it to room temperature to obtain manganese oxide nanodots / carbon material.

[0033] The manganese oxide nanodots / carbon material prepared in this example was subjected to an X-ray diffraction (XRD) test, and the results are as follows: Figure 1 As shown, it can be seen that the position of the product peak conforms to the standard peak type of manganous oxide and carbon, proving that the product is a high-purity manganous oxide / carbon material.

[0034] Example 2

[0035] A method for preparing manganese oxide nanodots / carbon material comprises the following steps:

[0036] (1) Weigh 10 g of β-cyclodextrin, 0.5 g of sodium perchlorate, and 4.5 g of manganese nitrate respectively, add them into a beaker containing 100 mL of distilled water, and continue stirring to form a colorless transparent solution. Freeze the colorless solution and place it in a vacuum freeze dryer until it is completely dry to obtain a precursor.

[0037] (2) placing the precursor in a tube furnace, heating it to 700°C at a heating rate of 5°C / min under an argon atmosphere and keeping the temperature for 2 h. After completion, cooling it to room temperature to obtain manganese oxide nanodots / carbon material.

[0038] The manganese oxide nanodots / carbon material prepared in this embodiment was observed using a scanning electron microscope (SEM), and the results of magnification of 10,000 times and 200,000 times were as follows: Figure 2 and Figure 3 As shown. Figure 2 It can be seen that the carbon matrix material has a skeleton structure with micron-sized pores distributed in it, which is conducive to ion transmission. Figure 3 It can be seen that manganese oxide nanoparticles are evenly dispersed on the surface of the carbon material, and the diameters are approximately between 2 and 30 nm.

[0039] Example 3

[0040] A method for preparing manganese oxide nanodots / carbon material comprises the following steps:

[0041] (1) Weigh 10 g of β-cyclodextrin, 0.25 g of sodium perchlorate, and 9 g of manganese nitrate respectively, add them into a beaker containing 100 mL of distilled water, and continue stirring to form a colorless transparent solution. Freeze the colorless solution and place it in a vacuum freeze dryer until it is completely dry to obtain a precursor.

[0042] (2) placing the precursor in a tube furnace, heating the precursor to 800°C at a heating rate of 5°C / min under an argon atmosphere and maintaining the temperature for 4 h. After completion, the precursor is cooled to room temperature to obtain manganese oxide nanodots / carbon material.

[0043] The manganese oxide nanodots / carbon material prepared in this embodiment was observed using a transmission electron microscope (TEM). The results are as follows: Figure 4 It can be seen that the manganese oxide nanodots / carbon material has an obvious thin-layer carbon structure, with a large number of concave defects on its surface, and the manganese oxide nanodots are evenly distributed on the surface of the thin-layer carbon structure.

[0044] Example 4

[0045] A method for preparing manganese oxide nanodots / carbon material comprises the following steps:

[0046] (1) Weigh 10 g of γ-cyclodextrin, 1 g of sodium perchlorate, and 15 g of manganese sulfate respectively, add them into a beaker containing 100 mL of distilled water, and continue stirring to form a colorless transparent solution. Freeze the colorless solution and place it in a vacuum freeze dryer until it is completely dry to obtain a precursor.

[0047] (2) placing the precursor in a tube furnace, heating it to 800°C at a heating rate of 10°C / min under an argon atmosphere and keeping the temperature for 3 h. After completion, cooling it to room temperature to obtain manganese oxide nanodots / carbon material.

[0048] The manganese oxide nanodots / carbon material prepared in this embodiment was observed by X-ray photoelectron spectroscopy (XPS), and the 2p image of manganese element obtained was as follows: Figure 5 As shown, it is proved that manganese exists in the form of divalent manganese.

[0049] Example 5

[0050] A method for preparing manganese oxide nanodots / carbon material comprises the following steps:

[0051] (1) Weigh 10 g of β-cyclodextrin, 0.4 g of potassium perchlorate, and 9 g of manganese nitrate respectively, add them into a beaker containing 100 mL of distilled water, and continue stirring to form a colorless transparent solution. Freeze the colorless solution and place it in a vacuum freeze dryer until it is completely dry to obtain a precursor.

[0052] (2) placing the precursor in a tube furnace, heating it to 700°C at a heating rate of 10°C / min under an argon atmosphere and keeping the temperature for 5 hours, and then cooling it to room temperature to obtain manganese oxide nanodots / carbon material.

[0053] The manganese oxide nanodot / carbon material prepared in this example was used as the positive electrode material, metallic zinc was used as the negative electrode material, and a 2 mol / L zinc sulfate solution was used as the electrolyte to assemble an aqueous zinc ion battery. The electrochemical performance of the battery was then tested using a charge and discharge device. The results are shown in FIG. Figure 6 and Figure 7 As shown, where:

[0054] Figure 6 The figure is a charge and discharge test diagram of the battery at a current density of 200 mA / g. It can be seen that the specific capacity of the battery is 274.8 mAh / g, indicating that the battery has an excellent specific capacity.

[0055] Figure 7The figure is a charge and discharge test diagram of the battery at a high current density of 5 A / g. It can be seen that the specific capacity of the battery is 104.6 mAh / g, indicating that the battery has excellent rate performance.

[0056] Example 6

[0057] A method for preparing manganese oxide nanodots / carbon material comprises the following steps:

[0058] (1) Weigh 10 g of γ-cyclodextrin, 0.5 g of potassium perchlorate, and 20 g of manganese sulfate respectively, add them into a beaker containing 100 mL of distilled water, and continue stirring to form a colorless transparent solution. Freeze the colorless solution and place it in a vacuum freeze dryer until it is completely dry to obtain a precursor.

[0059] (2) placing the precursor in a tube furnace, heating the precursor to 800°C at a heating rate of 10°C / min under an argon atmosphere and maintaining the temperature for 4 h. After completion, the precursor is cooled to room temperature to obtain manganese oxide nanodots / carbon material.

[0060] The manganese oxide nanodot / carbon material prepared in this example was used as the positive electrode material, metallic zinc was used as the negative electrode material, and a 2 mol / L zinc sulfate solution was used as the electrolyte to assemble an aqueous zinc ion battery. Then, a charge and discharge device was used to perform multiple charge and discharge cycle performance tests at a current density of 200 mA / g. The results are as follows: Figure 8 As shown in the figure, it can be seen that after 100 cycles, the discharge capacity can still be retained at 61.4%, and the coulombic efficiency is kept close to 100%, indicating that the battery has good low-current cycle stability.

[0061] Example 7

[0062] A method for preparing manganese oxide nanodots / carbon material comprises the following steps:

[0063] (1) Weigh 10 g of β-cyclodextrin, 1.5 g of sodium perchlorate, and 9 g of manganese nitrate respectively, add them into a beaker containing 100 mL of distilled water, and continue stirring to form a colorless transparent solution. Freeze the colorless solution and place it in a vacuum freeze dryer until it is completely dry to obtain a precursor.

[0064] (2) placing the precursor in a tube furnace, heating the precursor to 700°C at a heating rate of 5°C / min under an argon atmosphere and maintaining the temperature for 5 h. After completion, the precursor is cooled to room temperature to obtain manganese oxide nanodots / carbon material.

[0065] The manganese oxide nanodots / carbon material prepared in this example was used as the positive electrode material, metallic zinc was used as the negative electrode material, and a 2 mol / L zinc sulfate solution was used as the electrolyte to assemble an aqueous zinc ion battery. Then, a charge and discharge device was used to perform multiple charge and discharge cycle performance tests at a high current density of 1 A / g. The results are as follows: Fig. 9 As shown in the figure, after 500 cycles, the discharge capacity can still be retained at 81.1%, and the coulombic efficiency is kept close to 100%, indicating that the battery has good high current cycling stability.

[0066] Example 8

[0067] A method for preparing manganese oxide nanodots / carbon material comprises the following steps:

[0068] (1) Weigh 10 g of β-cyclodextrin, 0.1 g of sodium perchlorate, and 0.5 g of manganese chloride respectively, add them into a beaker containing 100 mL of distilled water, and continue stirring to form a colorless transparent solution. Freeze the colorless solution and place it in a vacuum freeze dryer until it is completely dry to obtain a precursor.

[0069] (2) placing the precursor in a tube furnace, heating it to 600°C at a heating rate of 5°C / min under an argon atmosphere, and then keeping the temperature for 6 h. After completion, cooling it to room temperature to obtain manganese oxide nanodots / carbon material.

[0070] The manganese oxide nanodot / carbon material prepared in this example was used as the positive electrode material, metallic zinc was used as the negative electrode material, and a 2 mol / L zinc sulfate solution was used as the electrolyte to assemble an aqueous zinc ion battery. Then, a charge and discharge device was used to perform a charge and discharge test on the battery at a current density of 200 mA / g. As a result, the specific capacity of the battery was 261.7 mAh / g, indicating that the battery had an excellent specific capacity.

[0071] Example 9

[0072] A method for preparing manganese oxide nanodots / carbon material comprises the following steps:

[0073] (1) Weigh 10 g of β-cyclodextrin, 2 g of sodium perchlorate, and 25 g of manganese carbonate respectively, add them into a beaker containing 100 mL of distilled water, and continue stirring to form a colorless transparent solution. Freeze the colorless solution and place it in a vacuum freeze dryer until it is completely dry to obtain a precursor.

[0074] (2) placing the precursor in a tube furnace, and heating the precursor to 1000°C at a heating rate of 5°C / min under an argon atmosphere and keeping the temperature for 1 h. After completion, the precursor is cooled to room temperature to obtain manganese oxide nanodots / carbon material.

[0075] The manganese oxide nanodot / carbon material prepared in this example was used as the positive electrode material, metallic zinc was used as the negative electrode material, and a 2 mol / L zinc sulfate solution was used as the electrolyte to assemble an aqueous zinc ion battery. Then, a charge and discharge device was used to perform a charge and discharge test on the battery at a high current density of 5 A / g. As a result, the specific capacity of the battery was 116.9 mAh / g, indicating that the battery has excellent rate performance.

[0076] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A manganese oxide nanodot / carbon material, characterized in that: The invention comprises a flaky carbon matrix material and manganese oxide nanoparticles distributed on the matrix material, and the matrix material is provided with a plurality of pit-shaped depressions; the preparation method of the manganese oxide nanodot / carbon material comprises the following steps: adding a carbon source, a perchlorate and a manganese source to water and stirring evenly, freeze-drying the obtained precursor liquid, and then calcining the obtained solid product in a protective atmosphere, and washing and drying the obtained product after completion, so as to obtain the obtained material; the carbon source comprises at least one of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin; The thickness of the flaky carbon matrix material ranges from 10 to 100 nm; The diameter of the manganese oxide nanoparticles is 2 to 30 nm; The mass ratio of the carbon source, perchlorate and manganese source is 10:(0.1-2):(0.5-25).

2. The manganese oxide nanodot / carbon material according to claim 1, characterized in that: The manganese source includes at least one of manganese nitrate, manganese sulfate, manganese carbonate, manganese chloride and manganese acetate.

3. The manganese oxide nanodot / carbon material according to claim 1, characterized in that: The perchlorate includes at least one of lithium perchlorate, sodium perchlorate and potassium perchlorate.

4. The manganese oxide nanodot / carbon material according to claim 1, characterized in that: The calcination treatment temperature is 600-1000°C, and the holding time is 1-6h.

5. The manganese oxide nanodot / carbon material according to claim 1, characterized in that: The protective atmosphere includes any one of nitrogen and argon.

6. Use of the manganese oxide nanodots / carbon material according to any one of claims 1 to 5 in the positive electrode of an aqueous zinc ion battery.

Citation Information

Patent Citations

  • Method using biogel carbonization to prepare double-layer carbon-wrapped manganous oxide electrode material

    CN106981643A

  • Bio-derived porous carbon prepared by micro-explosion and application of bio-derived porous carbon in supercapacitor

    CN111977652A

  • Aqueous zinc ion battery positive electrode material, preparation method thereof and aqueous zinc ion battery

    CN112838198A